2008
DOI: 10.1117/12.796016
|View full text |Cite
|
Sign up to set email alerts
|

The lithography technology for the 32 nm HP and beyond

Abstract: When using the most advanced water-based immersion scanner at the 32nm node half-pitch, the image resolution will be below the k1 limit of 0.25. In this paper, we will explore the capability of using the double pattern technique (DPT) to extend the resolution capability of the water-based immersion lithography and examine the readiness of EUV to carry the lithography resolution capability beyond the 32 nm HP.The DPT, whether done in two litho and etch steps (LELE) or using the side wall spacer and sacrificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…An improvement of approximately 3% is observed at all levels of misalignment across the range tested. Dusa et al 3 reported that the registration observed between two layers of a double patterning process in the dense pattern structure was considerably better than the reported registration between the two layers using standard box-in-box alignment measurements. The simulated results are consistant with these practical observations although the magnitude of the simulated improvement is significantly less than the reported experimental effects.…”
Section: Rcwa Simulation Results With Embedded Topographymentioning
confidence: 95%
“…An improvement of approximately 3% is observed at all levels of misalignment across the range tested. Dusa et al 3 reported that the registration observed between two layers of a double patterning process in the dense pattern structure was considerably better than the reported registration between the two layers using standard box-in-box alignment measurements. The simulated results are consistant with these practical observations although the magnitude of the simulated improvement is significantly less than the reported experimental effects.…”
Section: Rcwa Simulation Results With Embedded Topographymentioning
confidence: 95%
“…The favorite industrial approaches for the patterning of nanoscale devices smaller than that limit are various kinds of double or even quadruple patterning. In Litho-Etch-Litho-Etch (LELE) [22] and Litho-Freeze-Litho-Etch (LFLE) [23] the number of features is doubled and the pitch size halved, by exposing the wafer twice with two different masks (e.g., the mask shifted by half the pitch for the second illumination), employing some memory process of the photoresist and finally developing the resist after the second illumination. Consequently, focus and especially dose variations are not correlated between these two incremental lithography steps.…”
Section: Resultsmentioning
confidence: 99%
“…Possible candidates include contrast enhancement layer (CEL) 1 and two-photon absorption materials 2 . Figure 2b shows the logic extension of the litho-etch-litho-etch (LELE) 3 to litho-etch-litho-etchlitho-etch (LELELE). In this process, at least two hardmasks with good etch selectivity are required for pattern transfer.…”
Section: Higher Order Pitch Division Lithographymentioning
confidence: 99%